PENGEMBANGAN MESIN PAKAN OTOMATIS MEMANFAATKAN ENERGI MATAHARI UNTUK BUDIDAYA BIOTA AIR SEBAGAI SALAH SATU SOLUSI KETAHANAN PANGAN DAN PEMANFAATAN ENERGI TERBAHARUKAN DI MASA PANDEMI - Ichsan Setiawan; Sarwo Edhy Sofyan; Taufiq Saidi; Syarifah Meurah Yuni; Lulusi Lulusi; Said Amir Azan; Akram Tamlicha (Jurnal Marine Kreatif, 2021)
The province of Aceh is known for its coastal area which has enormous potential for the development of aquaculture of aquatic biota, both freshwater and saltwater communities. The potential for production from freshwater and saltwater fish businesses will be even more exciting in 2021. This is because the amount of fish consumption per capita of the world's population reaches 19.6 kg per year. This value is obtained from the results of estimates through the United Nations Food Agency in 2011. For this matter, various matters relating to the cultivation system must be prepared, starting from the stage of the enlargement process to the stage of feeding or baiting which is more regular and has precise calculations. The purpose of making this automatic feed machine product is to make it easier for aquatic biota cultivators the process of feeding aquatic biota in ponds and ponds through the development of an automatic feed distribution system equipped with systematic timing. With this equipment, the perpetrators of cultivating aquatic biota are able to provide feed easily and regularly so that it helps avoid aquatic biota experiencing a lack of feed which ends in death. The biggest benefit is that cultivators have time savings as well as labor cost savings. The results of this equipment manufacture in the form of a feed control system and feed spreader automatically assisted by the supply of solar power directly to the solar panel so that it is able to convert light energy and sunlight into electrical energy. The output of this product is expected to be able to provide the right solution to cultivators in increasing income and making it easier to use easy and efficient tools.